Changes in the physical, mental, spiritual and social health of ukrainians under the influence of stress factors of wartime (Environment & Health, 2025)
The purpose of the study was to identify, using a questionnaire survey, the impact of stress factors of martial law on various aspects of the health of the population of Ukraine.Materials and methods. The source of initial information was the data of an online survey of citizens in various cities of Ukraine and abroad. 1290 people aged 17 to 86 years participated in the survey. The methods used were: theoretical (analysis and generalization of literary sources; empirical (questionnaire survey) and methods of mathematical statistics (correlation analysis, Student and Pearson test; data rescaling method). The results were considered reliable at a significance level of p
Keywords: questionnaire; martial law; population health; adverse social factors; self-assessment of health